2018
DOI: 10.1186/s12906-018-2128-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antileishmanial and cytotoxicity activities of essential oils from Haplophyllum tuberculatum A. Juss leaves, stems and aerial parts

Abstract: BackgroundPlants used for traditional medicine produce diverse and complex secondary metabolites exhibiting various medicinal properties. The medicinal plant Haplophyllum tuberculatum is used by native people against malaria and parasitic infections.MethodsIn this study and in order to contribute for the search of new natural drugs for leishmaniasis, the essential oils of H. tuberculatum leaves, stems and aerial parts (leaves+stems) collected in two different periods, 2013 and 2015, and their components by GC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…sihthotpiana , E. tournefortii , E. orientalis , E. chrysantha , and E. lamondiana [35] . Piperitol was also very common compound in EOs of some plant species such as Mentha longifolia , [36] Cymbopogon schoenanthus , [37] and Haplophyllum tuberculatum [38] . The multitude of the monoterpene hydrocarbon compounds, terpinene, and cymene derivatives, were already reported in the EO of the two samples of D. tortuosa collected from Wadi Hagul and west Alexandria, Egypt [31] .…”
Section: Resultsmentioning
confidence: 82%
“…sihthotpiana , E. tournefortii , E. orientalis , E. chrysantha , and E. lamondiana [35] . Piperitol was also very common compound in EOs of some plant species such as Mentha longifolia , [36] Cymbopogon schoenanthus , [37] and Haplophyllum tuberculatum [38] . The multitude of the monoterpene hydrocarbon compounds, terpinene, and cymene derivatives, were already reported in the EO of the two samples of D. tortuosa collected from Wadi Hagul and west Alexandria, Egypt [31] .…”
Section: Resultsmentioning
confidence: 82%
“…These results suggest that HP has toxicity on cancer cells while protecting the normal ones. Previous studies on HP have shown that its essential oils have potentially protective effects on oxidative stress, highly cleaning efficacy and protective effects on human stroma U373-MG cells against H2O2 damage 15,16 . It has been proven that essential oils inhibit ROS production caused by H2O2.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic of the oils studied is its richness in sesquiterpenes, the thing which makes it different from other essential oils studied in other regions which are in their majority rich in oxygenated monoterpenes and monoterpene hydrocarbons. Thus, studies conducted on H. tuberculatum collected in Tunisia: 33 they showed that the essential oils of this plant was rich in monoterpenoids (20.7% for monoterpenic hydrocarbons, 46.7% for oxygenated monoterpenes and 0. 5% for sesquiterpene hydrocarbons), while on the other hand the study showed the richness of the essential oils of this plant in trans-p-menth-2-en-1-ol (18.23%), β-phellandrene (14.46%), piperitone (14.33%), cis-p-menth-2-en-1-ol ( 13.66%) and α-phellandrene (4.36%).…”
Section: Yield and Chemical Composition Of Essential Oilsmentioning
confidence: 99%